Diet and nutrition information on nine national cancer organisation websites: A critical review. (8th July 2020) - Barrett, Michelle; Uí Dhuibhir, Pauline; Njoroge, Catherine; Wickham, Sheelagh; Buchanan, Paul; Aktas, Aynur; Walsh, Declan
Abstract: Introduction: National Cancer Organisations (NCO) provide web‐based diet and nutrition information for patients with all types and stages of cancer. We examined diet and nutrition information provided by nine NCO in English‐speaking countries. Methods: Diet and nutrition information was examined under four headings: disease phases, treatment modalities, nutrition impact symptoms and cancer primary sites. We also examined the degree of concordance between NCO websites and appraised the readability of materials. Results: Nine NCO websites from six English‐speaking countries were included: Australia, Canada, Ireland, New Zealand, the United Kingdom and the United States. All provided general healthy eating advice. Information at diagnosis and pre‐treatment was inadequate, but well‐addressed for survivorship. Specific treatment modalities such as biological and hormone therapy were largely ignored. Symptom management was well‐addressed, with some exceptions. Cancer site‐specific advice was readily available. All recommended consultation with a dietitian/healthcare professional for personalised guidance. Only one met the universal health literacy standard. Conclusions: NCO websites provided important general diet and nutrition information for cancer patients. The information was reliable and safe, but more in‐depth, evidence‐based and health‐literate information is required. There is an urgent need for an international consensus for consistent cancer diet and nutrition advice.